2019
DOI: 10.1002/alr.22288
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 clinical study to assess the safety of a novel drug delivery system providing long‐term topical steroid therapy for chronic rhinosinusitis

Abstract: Background Chronic rhinosinusitis (CRS) patients who fail medical management have few treatment options other than endoscopic sinus surgery (ESS). A novel biodegradable mometasone furoate drug delivery system (LYR‐210) providing continuous topical steroid therapy to sinonasal mucosa over 24 weeks was developed to treat unoperated CRS patients who have failed medical management prior to ESS. LYR‐210 was designed to slowly expand in the middle meatus, ensuring efficient drug delivery as mucosal swelling reduces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…LYR-210 demonstrated a reproducible treatment effect in surgically naive CRS patients regardless of polyp status in 2 different clinical studies. The CFBL on the SNOT-22 over the 24-week treatment period observed for LYR-210 (2500 µg) in the LANTERN Phase 2 study is consistent with that of LYR-210 of the same dose in a phase 1 study, 12 which further validates the findings of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…LYR-210 demonstrated a reproducible treatment effect in surgically naive CRS patients regardless of polyp status in 2 different clinical studies. The CFBL on the SNOT-22 over the 24-week treatment period observed for LYR-210 (2500 µg) in the LANTERN Phase 2 study is consistent with that of LYR-210 of the same dose in a phase 1 study, 12 which further validates the findings of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Excluded from this review are reports of drug-eluting biomaterials that are intended to be placed in the office setting. These technologies include the Sinuva (Intersect ENT) 41,42 and LYR-210 implants (Lyra Therapeutics), 43 both of which have also shown clinical benefits for patients with CRS. The Sinuva steroid-releasing stent, which is placed into a previously opened ethmoid cavity for recurrent nasal polyposis, has received FDA approval for use since 2017, whereas LYR-210 is currently in phase 2 clinical development for treatment in surgically naive patients with CRS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patients in this single cohort trial had also undergone sinus surgery and were permitted to use saline irrigations. More recently, a Phase I open‐label, single‐arm study 17 of an alternate mometasone eluting stent design (2500 µg over 24 weeks) was reported with an –16.8‐point to –31.5‐point improvement in SNOT‐22 between weeks 8 to 24 in 20 patients.…”
mentioning
confidence: 99%